Physiology of reproduction in applications up to the animal industry - Monge M., Carlos (1942)
In 1931, the author, basing his observations on humans and on animals, stated the problem of fertility in the Andean plateau. Those men who live in the Andes, reproduce the same as those in the sea level. The same can be said of the animals of that region, and particularly those which have been acclimated for 400 years. Concerning animals, newly arrived to high lands, they show a diminution (50 to 60 70) in their fertility. The author describes the possible causes of this phenomenon. He points out the various methods of Electro ejaculation, which permit the obtaining of semen, when desired. He also indicates the occurrence of spermatogenesis in cats and rabbits at 4000 mts. above sea level. The author studies the characteristics of the standard semen of animals (rams ) and gives directive methods of research for verifying his hypothesis. Having once determined the "Standard Semen" of the altitude, the author concludes on the possibilities of improving fertility by selecting acclimatized rams. Disregards the problem of so called "machorras" (infertile ewes ) as he has obtained 86 % of fertility, and makes a comparative study of the races best suited for acclimatization.